INTERNALISASI NILAI KEARIFAN LOKAL DALAM PEMBELAJARAN IPS SEKOLAH DASAR UNTUK MEMBENTUK KARAKTER GLOBAL MENDUKUNG SDGS 4 - Priyono Tri Febrianto; Ramzi Albani Thariq; Shinta Nuriah; Fara Medinna Oktavia; Vero Stantika; ST. Shafiyatul Hasanah (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The development of globalization, characterized by advances in information and communication technology, has had a significant impact on the world of education, especially in the formation of the character of students. Widespread access to information brings great opportunities to increase global knowledge and insight, but also presents challenges in the form of the inclusion of external cultural values that have the potential to shift local cultural values. This research aims to analyze the internalization of the value of local wisdom in social studies learning in elementary schools as an effort to shape the global character of students and their relationship with the achievement of SDGs 4 regarding quality education. The method used is literature review by collecting, reviewing and analyzing various scientific sources such as journals, books and relevant documents. The results of the study show that local wisdom has an important role as a source of material as well as a contextual approach that is able to increase understanding of concepts, life skills, and instill character values such as mutual cooperation, responsibility and tolerance. Internalization strategies are carried out through active learning such as Project Based Learning, Problem Based Learning, and contextual approaches. The role of the teacher is also very important as a facilitator, guide and role model. This integration supports the realization of inclusive, relevant and sustainable education.